Impact of suction and thermal radiation on unsteady ternary hybrid nanofluid flow over a biaxial shrinking sheet - Wahid, Nur Syahirah; Md Arifin, Norihan; Yahaya, Rusya Iryanti; Khashi'ie, Najiyah Safwa; Pop, Ioan (Elsevier, 2024)
The use of hybrid nanofluids in practical applications is pivotal for enhanced heat transfer efficiency especially for electronics cooling, and manufacturing processes. This study delves into numerically investigating the unsteady water-based (alumina+copper+titanium dioxide) ternary hybrid nanofluid flow over a permeable biaxial shrinking sheet, considering the influence of thermal radiation. The model, initially formulated as partial differential equations (PDEs), is adeptly transformed into ordinary differential equations (ODEs) via established similarity transformations. Subsequently, a numerical solution employing the finite difference scheme in bvp4c MATLAB unravels the behaviors of crucial physical quantities—across various parameter configurations. Remarkably, this study reveals the presence of two potential solutions, among which only one exhibits physical stability. Notably, the findings underscore the efficacy of enlarging the boundary suction parameter and diminishing thermal radiation for augmenting heat transfer within the specified conditions of ternary hybrid nanofluid. A noteworthy finding of this study reveals that an increase in the boundary suction parameter by 4% leads to a remarkable 9% delay in the boundary layer separation of the ternary hybrid nanofluid, thus maintaining the laminar phase flow. This study offers crucial guidance and insights for researchers and practitioners delving into the mathematical or experimental aspects of ternary hybrid nanofluid dynamics.